Adsorption of Malachite Green Dye by Magnetic Carboxymethyl Chitosan - Kurniasih, Mardiyah; Setyaningtyas, Tien; Riyani, Kapti; Luthfia, Adilla; Aghniya, Imtiyazul (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2024)
Malachite green dye is widely used in the textile industry. Wastewater contaminated with malachite green dye threatens aquatic life and human health. Therefore, adsorption is needed in the dye waste treatment process. This research aims to synthesize magnetic carboxymethyl chitosan as an adsorbent for malachite green dye. Magnetic carboxymethyl chitosan was synthesized via a coprecipitation method and analyzed using FTIR. Batch experiments were used to study the adsorption of malachite green dye under adsorption parameters, such as the effects of pH and time, adsorption kinetics, isotherms, and reusability. The research results show that at pH 4, malachite green adsorbed most effectively into magnetic carboxymethyl chitosan. The pseudo-second-order kinetic model and the Langmuir adsorption isotherm model describe the adsorption process. Reduction for malachite green chitosan, carboxymethyl chitosan, and magnetic carboxymethyl chitosan were 34.19, 83.24, and 91.34%, respectively.